Capital financeiro e land grabbing: o controle de terras pela Agrifirma Brasil Agropecuária S.A - Silva, Lucas Antunes Leite da [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
This research is based on the idea that financial agents are imposing a new dynamic in world agriculture. Since the beginning of the twenty-first century, the increase in demand for commodities along with the global financial crisis has paved the way for the interest of financial investors in controlling land. This is because, despite their low liquidy, they are a safe investment, with a high pricing perspective. This situation led to a rush for land by the financial capital that became popular by the term Land Grabbing. By participating in agricultural production circuits, financial investors impose their logic of profitability on companies and the territory. This change in territorial dynamics bring with it new technical and normative contents, among them: productive specialization, a new territorial division of labor, an intensification in technology to maintain high levels of production, increasing land concentration and the number of conflicts. The challenge of this work is to analyze the strategies of action and accumulation of the agricultural company Agrifirma Brasil Agropecuária S.A. in the Brazilian territory. In this way, the research proposes: to trace the route of this company; identify and characterize the company's controlling financial agents, as well as their forms of partnership from the global to the local scope. In addition, an analysis will be made of Agrifirma's strategy of acquiring, pricing and selling land

Esta pesquisa parte-se da ideia que os agentes financeiros vêm impondo uma nova dinâmica na agricultura mundial. Desde o início do século XXI, o aumento da demanda por commodities junto à crise financeira mundial, abriu caminho para o interesse de investidores financeiros no controle de terras. Isto porque, apesar delas apresentarem uma liquidez baixa, são um investimento seguro, com alta perspectiva de precificação. Essa conjuntura levou a uma corrida por terras pelo capital financeiro que se popularizou pelo termo Land Grabbing. Ao participar dos circuitos produtivos agrícolas, os investidores financeiros impõem sua lógica de rentabilidade às empresas e ao território. Essa mudança na dinâmica territorial, traz consigo novos conteúdos técnicos e normativos, entre eles: a especialização produtiva, uma nova divisão territorial do trabalho, uma intensificação em tecnologia para manter níveis de produção elevados, o aumento da concentração fundiária e do número de conflitos. O desafio desse trabalho é analisar as estratégias de atuação e acumulação da empresa agrícola Agrifirma Brasil Agropecuária S.A. no território brasileiro. Desta maneira, a pesquisa propõe: traçar o percurso dessa empresa; identificar e caracterizar os agentes financeiros controladores da empresa, assim como suas formas de parceria desde o âmbito global até o local. Ademais foi feita uma análise sobre a estratégia da Agrifirma de aquisição, precificação e venda de terras
Keywords: Capital (Economia); Agropecuaria; Finanças; Agricultura; Agronegócio; Proprietarios de terras; Brasil